Strenghthening Competitiveness For SMES: A Conceptual Framework: Strenghthening Competitiveness For SMES: A Conceptual Framework - Lucas Magalhaes; Arif Dwi Hartanto (Jurnal Mantik, 2020)
The development of SMEs has very important role in creating employment and reducing poverty. However, the intensity of business competition is very high too, so the SMEs need to have the strength of competitiveness in order to sustain in the business world. Therefore, the purpose of this paper is to identify the main factors influencing the success of the SME competitiveness. Exploration is used as the basis approach for the analysis, in which the flexibility and productivity of the business become the main aspects. The results showed that the ability of SMEs in building a network effectively and efficiently is a determinant of the level of flexibility and productivity of SMEs. The network characteristics are marked by three conditions, namely (i) the efficiency of business by minimizing transaction costs, (ii) the increase of working capital accessibility, and (iii) the innovative business climate. The analysis provides important insights for the government that the efficient and effective expansion of the business network should be focused on the SME development policy.